Organización y archivo de los documentos e inventario de los activos fijos del GAD Parroquial de Toacaso del cantón Latacunga - Salazar Cofre, Blanca Cecilia (2016)
The present research work has as aim to apply the archiving system of documents and inventory of the fixed assets of the Toacaso Gad Parish of Latacunga Canton, the Autonomous Government works for the welfare of the Parish, communities, neighborhoods and associations belonging to it. With the handling of administrative documents based on the knowledge put into practice by the people who have performed in the daily activities that was determined by the application of methods, techniques and research instruments. The present thesis developed the organization and archives of the documents with the Parish GAD has, the job work allowed to classify, organize and file all the active documents of the Parish Government, which facilitated to the administrative staff the improveme, of the handling of the files, in order to improve the quality of the service in the public institution and consequently provide a better attention to the users of these dependencies. The inventory of fixed assets of the GAD Parish is made based on the provisions given by the Contraloria General Del Estado for the control of assets, allowing the proper control of the management of both physical and technological assets. So that there is a more adequate revision in each one of the GAD Parish dependencies.